Entrepreneurial intention and academic training: a study with academics of administration in a public institution (Research, Society and Development, 2020)
The purpose of this study is to investigate the influence of academic training on the entrepreneurial intention of the administration students from UEPB of Patos-PB. Characterized as a qualitative, participatory and descriptive research, the present investigation had its data collection conducted by a semistructured interview protocol with 21 (twenty one) administration students. The analysis of the results was based on an analysis of the content from which four categories emerged, from which it can be concluded that the administration students have entrepreneurial characteristics, but even with this entrepreneurial profile, some prefer not to follow in the area, others are already entrepreneurs and others have the will. Regarding the influence of the academic formation in relation to the entrepreneurial intention, the research presented a positive result, since the course exerts influence for the entrepreneurial intention, however, for those who have the entrepreneurial spirit and the preparation that the course offers to undertake did not obtain a relevant result, since it left to be desired in the feeling of relating the theory with the practice.